CONFLICT BETWEEN LAW AND JUSTICE - Widodo Dwi Putro (Jurnal IUS Kajian Hukum dan Keadilan, 2013)
The consequence of identifying justice with law is that seeking justice becomes constrained and it becomes limited only to the formulation of law. Although it is possible to approach justice from the ‘legal-formal’ aspect, justice cannot be reduced to law. Once justice is reduced to law, seeking justice outside the legal system ceases. The assumption that justice is identical to law is misleading, as justice is assumed to be inherent in the law itself. On the other hand, it is dangerous to make a distinct separation between law and justice. Law obtains its validity through its positive form, which is derived from the sovereign authority. The implication of this is that law is the law itself, altogether separate from justice, whereby an emphasis is placed only on its formal manifestation. However, law is not justice. Law is a calculable element, while justice is incalculable in concrete terms. Law is a tool for approaching justice. Therefore, law cannot possibly surpass justice, because assuming that law surpasses justice would be as stating that the tool colonizes its objective.